Use of cone-beam computed tomography and three-dimensional modeling for assessment of anomalous pulp canal configuration: a case report - Alper Sinanoglu; Dilek Helvacioglu-Yigit; Ibrahim Mutlu (Korean Academy of Conservative Dentistry, 2015)
Three-dimensional (3D) reconstruction of cone-beam computed tomography (CBCT) scans appears to be a valuable method for assessing pulp canal configuration. The aim of this report is to describe endodontic treatment of a mandibular second premolar with aberrant pulp canal morphology detected by CBCT and confirmed by 3D modeling. An accessory canal was suspected during endodontic treatment of the mandibular left second premolar in a 21 year old woman with a chief complaint of pulsating pain. Axial cross-sectional CBCT scans revealed that the pulp canal divided into mesiobuccal, lingual, and buccal canals in the middle third and ended as four separate foramina. 3D modeling confirmed the anomalous configuration of the fused root with a deep lingual groove. Endodontic treatment of the tooth was completed in two appointments. The root canals were obturated using lateral compaction of gutta-percha and root canal sealer. The tooth remained asymptomatic and did not develop periapical pathology until 12 months postoperatively. CBCT and 3D modeling enable preoperative evaluation of aberrant root canal systems and facilitate endodontic treatment.